2015
DOI: 10.1039/c5ce01364j
|View full text |Cite
|
Sign up to set email alerts
|

Divergent 4,2′:6′,4′′- and 3,2′:6′,3′′-terpyridines as linkers in 2- and 3-dimensional architectures

Abstract: This Highlight illustrates the strategies applied to encourage the formation of 2- and 3-dimensional metal–organic architectures as opposed to 1-dimensional chains using 4,2′:6′,4′′- and 3,2′:6′,3′′-terpyridines as organic linkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 51 publications
0
71
0
1
Order By: Relevance
“…[22,31] During the course of our investigations of the coordination chemistry of the ferrocenyl-functionalized 4,2':6',4''-and 3,2':6',3''-terpyridines shown in Scheme 2, Tian and coworkers reported that 2 reacts with ZnCl2 and ZnBr2 to give the discrete metallohexacycles 9…”
Section: Coordination Polymer Versus Metallomacrocycle Assembly With mentioning
confidence: 99%
“…[22,31] During the course of our investigations of the coordination chemistry of the ferrocenyl-functionalized 4,2':6',4''-and 3,2':6',3''-terpyridines shown in Scheme 2, Tian and coworkers reported that 2 reacts with ZnCl2 and ZnBr2 to give the discrete metallohexacycles 9…”
Section: Coordination Polymer Versus Metallomacrocycle Assembly With mentioning
confidence: 99%
“…1,2,3 A 4,2':6',4''-tpy ligand presents a V-shaped building block, coordinating only through the outer N-donors. 1,2 Kröhnke 4 or Wang and Hanan 5 synthetic methodologies permit ready functionalization of the 4'-position of the tpy unit. If the functional group is non-coordinating, the common assembly motifs for architectures supported by 4,2':6',4''-tpy ligands are 1D-chains and 2D-sheets depending upon the coordination geometry of the metal nodes.…”
Section: Introductionmentioning
confidence: 99%
“…If the functional group is non-coordinating, the common assembly motifs for architectures supported by 4,2':6',4''-tpy ligands are 1D-chains and 2D-sheets depending upon the coordination geometry of the metal nodes. 1,2 The introduction of coordinatively non-innocent domains such as pyridyl 6 or carboxylate 7 moieties is a proven approach to increasing the dimensionality of 4,2':6',4''-tpy-based coordination assemblies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination chemistry of divergent 4,2’:6’,4”-terpyridine (4,2’:6’,4”-tpy) and 3,2’:6’,3”-terpyridine ligands is now a mature field, with the former ligand in particular being increasingly employed as a building block for the assembly of coordination polymers and networks [1,2]. There are a few examples of 4,2’:6’,4”-tpy ligands acting in a monodentate mode [3,4,5,6,7] but, typically, 4,2’:6’,4”-tpy coordinates through the two outer nitrogen atoms, with the central nitrogen atom non-coordinated.…”
Section: Introductionmentioning
confidence: 99%